RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND BALANCED NUTRITION DIET WITH NUTRITIONAL STATUS OF STUDENTS AT SMA NEGERI 3 BALIKPAPAN DURING ONLINE LEARNING - Tiksna Setya Waratmaja; Farapti Farapti; Emyr Reisha Isaura (Media Gizi Indonesia, 2022)
The students experience the impact of the COVID-19 virus transmission. One of it was school from home. Online learning conditions allow adolescents to experience shifts in physical activity and diet patterns. This study analyzed the relationship between physical activity and a balanced nutritional diet with nutritional status in students at SMA Negeri 3 Balikpapan. This type of research was quantitative research with explanatory surveys and using a cross-sectional design. In this research, all active students of SMA Negeri 3 Balikpapan were involved as a population. The number of samples obtained was 92 people using purposive sampling techniques. An instrument for measuring activity level variables was the International Physical Activity Questionnaire-Short Form (IPAQ-SF). A balanced nutrition diet was assessed using Semi Quantitative-Food Frequency (SQ-FFQ) and the Balanced Nutrition Index 3 Levels (IGS3-60). Measurement of nutritional status through self-reporting based on body mass index by age z-score (BMI/Age). The statistical test used was a chi-square to test the research hypothesis. Based on the results of the chi-square statistical test, there was a relationship between physical activity and nutritional status (p=0,014), and there was no relationship between a balanced nutritious diet and the nutritional status (p=0,212). Physical activity is closely related to the nutritional status of adolescents. Therefore, to maintain optimal nutritional status, implementing a healthy lifestyle and physical activity patterns are need to be done.